Par reduction in OFDM through convex programming - Chao Wang; Shu Hung Leung (2008 IEEE International Conference on Acoustics, Speech and Signal Processing, 2008)
The high peak-to-average power ratio (PAR) encountered in OFDM system has been a major obstacle in the implementation of power efficient transmitter. In this paper, we present a new active constellation extension (ACE) based convex optimization algorithm which reduces PAR through convex programming. In comparison with previous convex programming method, our method greatly reduces the complexity and keeps the bit-error-rate (BER) performance. Moreover, our method can be combined with other clipping based ACE algorithms to further reduce the complexity with a slight performance degradation. Simulation results are given in this paper which show our method outperforms other ACE-based algorithms.